Proposals for Development Programme for the Year 1972-73 Part II Statements I to VIII Government of Gujarat - Planning Commission (Planning Commission, 1971)
The Kakrapar Project was taken up by Central Water and Power Commission, New Delhi in 1945-49, as a stage I Project of development of Tapi Valley, the stage-II being the Ukai Project-Kakrapar Project consists of a masonary weir across river Tapi, about 50 miles up stream of Surat. It is situated near village Kakrapar- Taluka Mandvi, Dist. Surat Gujarat State. The Project on completion Provides for an irrigation of 5,36,250 acres i.e. 2,17,230 Hector of cultivable command areas. The potential created up June 1971 is 5,00,760 acres i. e. 2,02,740 Hectors, and it is planned to develop the ultimate potential by June 1972.
Government of Gujarat, General Administration Department